ANALISIS DAMPAK LALU LINTAS AKIBAT RELOKASI PASAR HEWAN DI BANGSRI KABUPATEN JEPARA - hilmatunniyah, saqifah; Umam, Khotibul; Adi saputro, Yayan (Jurnal Civil Engineering Study, 2024)
This analysis is motivated by the relocation of the bangsri animal market which began operating on August 25, 2022 this causes an increase in traffic load and because the market is a new place in terms of parking there are still problems such as irregularity in parking vehicles. Therefore, it is necessary to analyze the traffic impact due to the relocation of the bangsri animal market, after the analysis is carried out, the capacity of the bangsri 4-signaled intersection with the highest approach is the western approach of 830.55 smp with the highest degree of saturation on the northern approach of 0.68 and the highest delay occurs on the northern approach of 30.4 sec /mp with category D. At the intersection 3 unsignalized jerukwangi the capacity of the intersection is 1231 smp and the level of service is 0.41 with category B. analysis using Vissim Software is carried out at intersection 4 signaled bangsri output level of service is LOS D and intersection 3 unsignalized output level of service is LOS A Parking space requirements at the bangsri animal market that must be provided for motorcycles 99 SPR, light vehicles 94 SPR, and heavy vehicles 22 SPR.